The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1159/000110611
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic Hypophysitis

Abstract: Background:Lymphocytic hypophysitis is a disorder of the pituitary gland that presents as a sellar mass lesion and/or hypopituitarism. It causes pituicyte destruction and hypopituitarism and is speculated to have an autoimmune basis. Diagnosis: Lymphocytic hypophysitis should be considered in the differential diagnosis of pituitary masses and/or hypopituitarism in females who are pregnant or in the early postpartum period, especially in cases associated with other autoimmune diseases or unusual patterns of hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 85 publications
0
62
0
3
Order By: Relevance
“…Lymphocytic hypophysitis (LYH), a rare chronic inflammatory disorder of the pituitary gland developed mainly by autoimmune processes, causes pituicyte destruction and hypopituitarism (1). LYH is usually classified in lymphocytic adenohypophysitis, which is characterized by lymphocytic infiltration limited to the anterior lobe of pituitary, and lymphocytic infundibulo-neurohypophysitis (LINH), which involves the infundibulum, stalk and neurohypophysis.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocytic hypophysitis (LYH), a rare chronic inflammatory disorder of the pituitary gland developed mainly by autoimmune processes, causes pituicyte destruction and hypopituitarism (1). LYH is usually classified in lymphocytic adenohypophysitis, which is characterized by lymphocytic infiltration limited to the anterior lobe of pituitary, and lymphocytic infundibulo-neurohypophysitis (LINH), which involves the infundibulum, stalk and neurohypophysis.…”
Section: Introductionmentioning
confidence: 99%
“…The patient had polyuria for three months before admission, which suggested that inflammation may have spread from the posterior to the anterior pituitary accompanied by aseptic meningitis. Unlike LAH, some cases of LINH have not shown any autoimmune disorders, and middle-aged or oldaged male subjects can be affected with LINH (11,12). A diagnosis of comorbid hypophysitis and aseptic meningitis was challenging because of the lack of a typical mass effect, such as headaches and visual impairment, and because of the gradual clinical course that mimicked subacute meningoencephalitis, including tuberculous, fungal and carcinomatous meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore unclear whether improvements in the clinical course of this disease can be directly attributed to glucocorticoid treatment or simply reflect a natural progression [30]. Because of the uncertainty regarding the efficacy of glucocorticoid treatment and its known adverse effects, the justification for this approach typically requires a mass effect due to a swollen pituitary [31]. In the case of IgG4-related hypophysitis (Table 5), patients were treated with various doses of glucocorticoid, from a replacement dose for adrenal insufficiency to a pharmacological dose.…”
Section: Case Reportmentioning
confidence: 99%